The effect of using the differentiated education strategy in developing grammatical skills in the Arabic language course among students of the scientific departments of the College of Education - Sana’a - Al-Gaadi, Ebrahim Esmail Abbas (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to know the effect of using the differentiated education strategy in developing grammatical skills in the Arabic language course among students of the scientific departments of the College of Education- Sana’a، based on the two approaches (descriptive and quasi-experimental). differentiated education، achievement test، The sample of the field study consisted of (41) male and female students from the first-level scientific departments who were registered in the two departments (Mathematics and Life Sciences) in the academic year (2021 AD- 2022 AD)، they represented one experimental group who were taught the grammatical skills prescribed to them in the book (Arabic Language 102) using the strategy differentiated education، The results of the study revealed that there were statistically significant differences at the significance level (0.05) between the mean scores of the experimental group in the two applications (pre and post) to test the grammatical skills at the test level as a whole and at the level of each independent skill in favor of the post application، attributed to the teaching of grammatical skills using the differentiated education strategy. The researcher recommended the inclusion of a differentiated education strategy within modern teaching methods to be taught in colleges of education.
Keywords: Strategy; differentiated education; grammatical skills